Effective credit & collection management : techniques and strategies - Andres, Tomas Quintin (Manila, Philippines : Rex Book Store, 1981)
"The book aims to give businessmen and credit men a throrough insight into the principles of credit and collection. It also aims to familiarize the credit and collection man with the latest techniques and advances in credit management, and the collection of accounts..."
Chapter I. The Collector's Job 1 -- Chapter II. The Credit Process 13 -- Chapter III. The Credit Analysis 29 -- Chapter IV. Credit Decision Making 48 -- Chapter V. Collection Policies, Procedure, Practices and Techniques 54 -- Chapter VI. Legal Dimensions of Credit and Collection 126 -- Chapter VII. The Implications of Filipino Values in Credit and Collection 143
Includes bibliographical references and index.
Keywords: CREDIT